CRISPR-Cas13d Exhibits Robust Antiviral Activity Against Seneca Valley Virus - Zhang, Yu-Yuan; Sun, Ming-Xia; Lian, Yuexiao; Wang, Tong-Yun; Jia, Mei-Yu; Leng, Chaoliang; Chen, Meng; Bai, Yuan-Zhe; Meng, Fandan; Cai, Xue-Hui; Tang, Yan-Dong (Frontiers in Microbiology, 2022)
In recent years, Seneca Valley virus (SVV) as a newly identified pathogen of porcine vesicular disease spread quickly and has posed a potential threat to the swine industry in several countries resulting in economic losses. Considering the evolution of SVV, attention should be given to controlling SVV epidemics. So far there are no commercial vaccines or drugs available to combat SVV. Therefore, development of strategies for preventing and controlling SVV infection should be taken into account. In the current study, we evaluated whether the CRISPR-Cas13d system could be used as a powerful tool against SVV infection. Besides, selected crRNAs showed different capacity against SVV infection. Our study suggests the CRISPR-Cas13d system significantly inhibited SVV replication and exhibited potent anti-SVV activity. This knowledge may provide a novel alternative strategy to control epidemics of SVV in the future.